2009
DOI: 10.1017/s095026880900212x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of hepatitis C in drug injectors: the role of homelessness, opiate substitution treatment, equipment sharing, and community size

Abstract: A prospective cohort study estimated the incidence of hepatitis C virus (HCV) in drug injectors in South Wales (UK). In total, 286/481 eligible seronegative individuals were followed up after approximately 12 months. Dried blood spot samples were collected and tested for anti-HCV antibody and behavioural data were collected at baseline and follow-up. HCV incidence was 5.9/100 person-years [95% confidence interval (CI) 3.4-9.5]. HCV incidence was predicted by community size [incident rate ratio (IRR) 6.6, 95% C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
89
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 32 publications
10
89
2
Order By: Relevance
“…Andia et al 84 likewise demonstrated that among Puerto Rican PWID homelessness was not associated with sharing syringes, but was associated with sharing other injecting equipment. Our results are consistent with previous research demonstrating that homeless PWID are more likely to inject in public spaces 43 ; and that public injecting is associated with frequent and hasty injecting and the sharing of injecting equipment. 38,43,86,87 Homelessness among PWID leads to their spending more time in environments where risk behavior is elevated 87 and, consequently, BBV acquisition is more likely.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Andia et al 84 likewise demonstrated that among Puerto Rican PWID homelessness was not associated with sharing syringes, but was associated with sharing other injecting equipment. Our results are consistent with previous research demonstrating that homeless PWID are more likely to inject in public spaces 43 ; and that public injecting is associated with frequent and hasty injecting and the sharing of injecting equipment. 38,43,86,87 Homelessness among PWID leads to their spending more time in environments where risk behavior is elevated 87 and, consequently, BBV acquisition is more likely.…”
Section: Discussionsupporting
confidence: 92%
“…50,65 Generally, however, the prevalence of housing instability among our sample appears lower than that documented in samples of North American PWID, which range from 16 % over an 8-year period 65 through to 47 % over a 10-year period 50 and up to 85 % lifetime history, 55 while documented rates of current and recent rates housing instability include 60, 53 62 51 , and 68 % 57 in Vancouver, and an average of 54 % across five US cities including Los Angeles and Seattle. 48 Likewise, estimates from studies in the UK also suggest higher prevalence of current and recent homelessness than we found among our sample, ranging from 44 % of 282 PWID in South Wales, 43 to 59 % of a community sample of 1,058 PWID recruited across seven sites in England. 56 Nevertheless, and as the international literature would predict, 50 housing is clearly a significant problem among PWID relative to the broader Australian population.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…However, this needs to be interpreted with care as those reporting needle exchange use in the last year will include not only those making extensive regular use of needle exchange services but also those making irregular or limited use of these services. Studies suggest the consistent high coverage of interventions like needle exchange is needed for them to be effective against bloodborne viruses [35][36][37], and it is likely that such coverage issues would similarly affect their impact on injection site infections. It should also be noted that not all needle exchanges in the UK provide a full range of injecting equipment, and that some IDUs may also have accessed a needle exchange service either as a route to wound care or as a preventive measure following an injection site infection.…”
Section: Discussionmentioning
confidence: 99%